Precompetition strategies to improve performance in endurance or repeated intermittent activity: Evidence and practical suggestions - Valcarce-Merayo, E.; Latella, C. (Strength and Conditioning Journal, 2023)
Athletes engage in training programs that develop physical and physiological attributes to improve performance over time. However, ensuring athletes are optimally prepared just before competition is also of utmost importance. Indeed, such approaches may often adopt 1 or more strategies in the days, hours, and minutes preceding competition, including exercise priming, active warm-up, and/or postactivation performance-enhancing (PAPE) activities. Despite a plethora of discrete research, such information seems poorly synthesized, making it difficult for coaches and athletes to implement optimal evidence-based physical preparation approaches in many sporting contexts. This article aims to provide a scoping overview of evidence, facilitate discussion, and where possible, propose practical exercise-based recommendations that may be useful leading up to (~48 hours-~1 minute) tasks with a short or prolonged endurance component or requiring repeated intermittent efforts (e.g., team-based field sports). Well-timed and -designed activities can facilitate several aspects of physical performance, potentially improve athletes' psychological state(s) and mental preparedness. The benefits of a warm-up are most well-documented, but priming and PAPE strategies also warrant consideration. It is intended that the evidence and suggestions presented will be useful for strength and conditioning professionals preparing athletes for competition.